Preliminary inventory of terrestrial Heteroptera from Lebanon (Hemiptera: Leptopodomorpha, Cimicomorpha and Pentatomomorpha) - Matocq, Armand; Azar, Dany (Zootaxa, 2023)
This paper gives, for the first time, a faunistic list of terrestrial Heteroptera (Leptopodomorpha, Cimicomorpha and Pentatomomorpha) known to occur in Lebanon. The list is based on examination and identification by the first author of specimens preserved in various collections and on reliable published records. A total of 231 species and subspecies belonging to 161 genera and 26 families are recorded for the country. Among these species, 71 belonging to 60 genera and 11 families are not cited in the Catalogue of the Heteroptera of the Palaearctic Region (Aukema & Rieger, 1995–2006; Aukema et al., 2013; Aukema 2018–2022), as being present in Lebanon, and thus may be considered as new for the country. A list of 18 species of terrestrial Heteroptera housed at the Lebanese University Collection is also given but these identifications need to be verified.